2014
DOI: 10.1111/hae.12553
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of immunogenicity to factor IX during the treatment of haemophilia B

Abstract: Inhibitors are an impediment to the effective management of haemophilia B (HB), but there is limited understanding of the underlying genetic risk factors. In this study we aim to understand the role of F9 gene mutations on inhibitor development in patients with HB. Mutations in the F9 gene were identified and HLA typing performed for five boys with severe HB. Data from the CDC Haemophilia B Mutation Project (CHBMP) database were used to assess association between F9 gene mutation type and inhibitor development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…41 These experiments demonstrated that the major histocompatibility complex (MHC) class II (H-2) and/or K class I-a (Iak) loci were critical to the inhibitor response. The role of the HLA alleles was also highlighted in the article from Saini et al, 34 in which only one of two siblings with inhibitors, an identical F9 mutation, but different HLA alleles, showed a response to immune tolerance induction (ITI). The HLA alleles of the individual patient, in conjunction with the mutation type, could be a predictor for the development of inhibitors, as well as the response to ITI.…”
Section: Risk Factors and Pathophysiologymentioning
confidence: 98%
See 2 more Smart Citations
“…41 These experiments demonstrated that the major histocompatibility complex (MHC) class II (H-2) and/or K class I-a (Iak) loci were critical to the inhibitor response. The role of the HLA alleles was also highlighted in the article from Saini et al, 34 in which only one of two siblings with inhibitors, an identical F9 mutation, but different HLA alleles, showed a response to immune tolerance induction (ITI). The HLA alleles of the individual patient, in conjunction with the mutation type, could be a predictor for the development of inhibitors, as well as the response to ITI.…”
Section: Risk Factors and Pathophysiologymentioning
confidence: 98%
“…31,32 On the other hand, in HB patients, complete deletions or rearrangements of F9 ($50%) and nonsense or frameshift mutations ($20%) carry an increased risk of inhibitor occurrence; gene inversions, related with inhibitor risk in HA, have not been identified in HB patients. 12,33,34 The ISTH Scientific and Standardization Committee International FIX inhibitor registry (ISTH-SSC registry; 1997-2006) analyzed 94 patients with severe HB and an inhibitor. 3 Thirty-two of 94 patients underwent genetic analysis demonstrating that large deletions and nonsense mutations were associated with both inhibitor development and risk of anaphylaxis.…”
Section: Risk Factors and Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact the postinfusion peak was 55.4% with a IVR of 0.81, and the ileo-psoas haematoma was resolved quickly without sequelae. Although the patient was able to self-infuse, we decided to treat him in the first Large delections or null mutations 11,12 were reported as associated to high risk of inhibitor development and could explain the appearance of these allo-antibodies also in cases of PTPs after multiple exposures to FIX concentrates. A nonsense mutation in FIX gene (p.Arg298Stop) was also related to an anaphylactic reaction as reported by Cugno et al 13 In our patient, the gene mutation that caused his disease is a splice mutation at the exon 2 (intron 2), c.252+G>A.…”
mentioning
confidence: 99%
“…Individuals with large gene deletions, frameshift, and nonsense mutations are usually CRM À and are most susceptible to the development of inhibitors against FIX, accounting approximately for 70% of cases, while missense mutations, which constitute the majority of genotypes in HB, are at very low risk of inhibitor formation. [13][14][15] The increased risk of inhibitors in patients carrying large gene deletions, frameshift, and nonsense mutations has prompted recommending mutation testing in severe HB patients to identify who are at risk for inhibitor development and anaphylactic reactions. 16 In addition, entity of risk in previously untreated severe HB patients is poorly known, as most studies do not provide specific information and that factors other than genotype have not been studied in such patients.…”
Section: Nonmodifiable Risk Factorsmentioning
confidence: 99%